Structural insights into the mechanism and E2 specificity of the RBR E3 ubiquitin ligase HHARI - Lingmin Yuan (Nature Portfolio, 2017)
HHARI is a RING-in-between-RING (RBR) ubiquitin (Ub) E3 ligase. Here the authors present the crystal structure of HHARI with the UbcH7 ~ Ub thioester intermediate mimetic, which reveals that HHARI binds this E2 ~ Ub in an open conformation and explains the specificity of this cognate RBR E3/E2 pair.